Social Media Usage And Its Impact On Work Productivity At A Malaysian University - Mohamed, Shahrulanuar; Sidek, Safiah; Izharrudin, Siti Zakiah; Kudus, Norliah; Abu Hassan, Mahadi; Rajikon, Muhd Akmal Noor (Blue Eyes Intelligence Engineering & Sciences Publication (BEIESP), 2019)
The ubiquity of social media at the workplace has motivated researchers to investigate its contribution to the work performance among employees. However, an investigation of this phenomena at a learning institution in Malaysia is still non-existence. Thus, this study aimed to explore the perceived impact of using social media to work productivity among employees at a particular university. A focus group interview among nine employees consisting of different job scope at an academic centre of a particular university has been conducted. Data were transcribed, coded and categorised using Nvivo Pro 11 software. The finding of this study showed the common social media used by the respondents are Whatsapp followed by email, Facebook, Youtube and Google via smartphone and desktop for work, notification and reminder purposes. Respondents highlighted the positive and negative impacts of using social media which affect their job productivity and showed different perceptions toward the relationship between the reasons of using social media and staff productivity. The findings were limited to a particular context hence generalising them to other context need to be done with caution. Further, this study can be considered as a preliminary study to gain further understanding of the impact of social media to work productivity.